Prevalence of diabetes mellitus in 2019 novel coronavirus: A meta-analysis. (June 2020) - Wang, Xiang; Wang, Shoujun; Sun, Liangge; Qin, Guijun
Abstract: Background: Since December 2019, a new strain of coronavirus named 2019 novel coronavirus (2019-nCoV) has been discovered in Wuhan. The prevalence of diabetes mellitus, which is a great public health issue leading to immunity inhibition and an increased incidence of infections, has been increasing over the past ten years. The aim of this research was to systematically assess the prevalence of diabetes mellitus among 2019-nCoV. Methods: We searched PubMed, Embase, Web of Science and Medline for observational studies up to February 25, 2020. A random effects model or fixed-effects model was applied to evaluate the pooled prevalence of diabetes mellitus and odds ratio (OR) with 95% confidence interval (CI). Findings: In total, nine papers met the eligibility criteria. The pooled prevalence of DM was 9% (95% CI 6%–12%). There was obvious heterogeneity (I 2 65%, p = 0.004) in the prevalence of DM in these studies. The prevalence of DM in moderate patients with 2019-nCoV was 7% (95% CI 4%–10%). The prevalence of DM in severe patients with 2019-nCoV was 17% (95% CI 13%–21%). The prevalence of DM in severe patients with 2019-nCoV was significantly higher than that in moderate patients with 2019-nCoV (OR 2.49, 95% CI 1.70 to 3.64). Interpretation: To our knowledge, this work is the first report showing the prevalence of diabetes mellitus in patients with 2019-nCoV, which is beneficial to prevent the spread of 2019-nCoV in the future.